Legal Aid in Indonesia: A Study of Legal Aid with a Transcendental Dimension - Fanny Dian Sanjaya (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2020)
Legal aid in Indonesia, particularly in terms of access to justice, legal aid provided by the state for people is still pivoted on positive law. Laws regulating legal aid in Indonesia remain revolving around the number of cases and budget absorption targets given to legal aid institutions that have been verified and accredited by the state for people/groups in need. Verification and Accreditation from the state with parameters written in the law inhibit those who need legal assistance if they are not categorized as the poor. The requirement of the poor to access legal aid implies that access to legal aid for everyone in conflict is far from justice. Access to legal aid is essential since the purpose of the law is justice. Besides, legal aid aims to provide justice for those who do not have law knowledge, in other words, blind to the law. Justice for all is the vein of legal aid which is inseparable from the right of legal aid for those in need. Legal aid can be administered by social institutions/legal aid agencies which should provide access to those who need legal assistance and those who are in dispute, be it poor or rich so that justice for all can be achieved. This research discusses the transcendental dimension of legal aid. This study used a descriptive research method intending to analyze legal aid from legal aid institutions viewed from the study of legal philosophy and legal aid with transcendental dimensions.